Something has shifted: Nursing students' global perspective following international clinical placements - Gower, Shelley; Duggan, Ravani; Earnest, Jaya; Boldy, Duncan (Blackwell Publishing Ltd, 2017)
© 2017 John Wiley & Sons Ltd. Aims: To examine understandings of global health issues among nursing students following participation in an international clinical placement during their pre-registration university education. Background: Universities use international clinical placements, especially in developing countries, to develop cultural awareness in students; however, little is known about the longer term influences on students' understandings of global nursing. Design: A retrospective cross-sectional design was used, using an exploratory, descriptive qualitative approach. Methods: Individual semi-structured interviews were conducted in 2014 with a purposive sample of 25 pre-registration nursing students from four Western Australian universities who undertook clinical placements across five countries. Data were analysed using inductive thematic analysis. Results: Findings highlight that students developed new understandings around health systems including fragility of resource access, differences in clinical practice and variances in nursing roles between settings. Students also experienced challenges but were able to appreciate alternative world viewpoints. Conclusion: International clinical placements can develop greater awareness and help students form realistic strategies for using their nursing skills globally. Pre-placement training in cultural awareness and health system realities, along with strong supervisory support, is critical to success.